Emotional support provided by nursing professionals and coping of parents of pediatric patients with congenital heart disease after surgery, INCOR 2014. - Manturano Velásquez, Gladys Norma (2019)
Objective: To determine the relationship between emotional support provided by the nurse and coping of parentsof pediatric patients with congenital heart disease after surgery. Methodology: The study corresponds to a nonexperimental design, quantitative, descriptive, correlational, cross-sectional type. The sample was composedby 44 parents of pediatric patients with congenital heart disease after surgery, a non-probability sampling wasused. To collect data two instruments were used. Results: There were: 27% of parents receive positive emotionalsupport and coping is favorable; 43% of parents receive adverse emotional support and coping is unfavorable.Applying statistical chi-square test, the relationship between the variables was significant p: .009; ie, the greaterthe emotional support of the nurse better coping parents of pediatric patients with congenital heart disease aftersurgery. In conclusion, emotional support in times of crisis it is vital to have a positive coping.